Great Expectations?! Assortment Size, Expectations, and Satisfaction - Diehl, Kristin; Poynor, Cait (Journal of Marketing Research, 2010)
Recent research challenges the idea that greater choice is always desirable, showing that larger assortments can increase choice deferral and switching. The current research demonstrates that even when consumers make a purchase, the same item may generate lower satisfaction when chosen from a larger rather than a smaller assortment. The authors explain this effect in terms of an expectation-disconfirmation mechanism. When assortments are small, consumers have low expectations about their ability to match their preferences. As assortment sizes increase, so do consumers’ expectations of the degree of preference match they can achieve. Subsequently, consumers may experience greater negative expectation disconfirmation or less positive expectation disconfirmation when a chosen item comes from a larger rather than a smaller set. Either less positive or more negative disconfirmation leads to lower choice satisfaction. The results from three studies support this expectation-based process and establish this mechanism in addition to alternative explanations, such as choice overload.